Analisis IT Service Management (ITSM) Menggunakan Framework ITIL V4 pada PT. PBM Bahari Raharja Permai - Fachrizal Fadhil Oktafian; Dicky Pratama (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Information technology plays an important role in supporting organizational operations, including in the cargo handling and logistics sector. However, studies on the implementation of ITIL V4 in logistics companies that integrate ERP Orlansoft and Inventory Management applications remain limited. This study aims to analyze the maturity level of IT service management at PT. PBM Bahari Raharja Permai using the ITIL V4 framework. The research methods include observation, interviews, questionnaires distributed to 13 respondents, SWOT analysis, and RACI mapping. The analysis focuses on the domains of Service Desk, Incident Management, Monitoring and Event Management, and Continual Improvement. The novelty of this study lies in the application of the ITIL V4 framework to evaluate IT services in a cargo handling company utilizing ERP Orlansoft and Inventory Management applications to support its operations. The results indicate that all domains achieved Level 4 (Managed), with scores of 3.85 for Service Desk, 3.96 for Incident Management, 3.74 for Monitoring and Event Management, and 3.73 for Continual Improvement. These findings provide an important basis for improving IT service quality in a structured manner and serve as a reference for ITIL V4 implementation in the logistics sector.